SMART POLICY: MENGADOPSI STRATEGI PEMERINTAH ESTONIA DALAM INDUSTRI KREATIF - Hartika Arbiyanti; Surfian Rahmat AP; Hendika Dwinanda Wicaksana (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
In the digital economy, the creative industry demands agile governance yet often encounters rigid regulatory frameworks. Estonia, a global digital pioneer, offers a